Intermedialer Style: Kulturelle Kontexte und Potenziale im literarischen Schreiben Jugendlicher - Wurzenberger, Gerda (transcript, 2016)
This volume focuses on the form of literary writing that is emerging from the lifeworld of young people. The »style« which is becoming increasingly evident in this context is innovative, and sometimes even avant-garde.